A Self‐Healing Electronic Sensor Based on Thermal‐Sensitive Fluids. (8th July 2015) - He, Yonglin; Liao, Shenglong; Jia, Hanyu; Cao, Yuanyuan; Wang, Zhenning; Wang, Yapei
<x xml:space="preserve">Abstract</x> A combination of liquid sensing materials and self‐healing polymers is conceived for preparing electronic sensors that can be mended when they suffer damage. The leakage of ionic liquids at a breaking state is avoided with the help of the capillary effect. Photothermal conversion and magnetic‐thermal conversion extend the sensing application. The successful development of self‐healing sensors is promising for exploiting high‐level electronic devices with long‐term service.